Age and sex-based differences in functional strength of adults participating in Special Olympics - Viviene A. Temple; Pauli Rintala; Shayla Zeitz; Meghann Lloyd; John T. Foley (European Federation of Adapted Physical Activity, 2022)
Muscular strength is a critical component of physical health. The aim of this cross-sectional study was to examine age- and sex-based differences in functional strength and rates of referral for education in a large international sample of Special Olympics athletes. A total of 30,358 (male = 19,661) adult (20-69 years old) athlete functional strength records were utilized from the Special Olympics Healthy Athletes database. Descriptive statistics were computed for the following tests: timed sit to stand, partial sit-up, grip strength, and seated push-up. Analyses of variance with Fisher-Hayter pairwise comparisons generally supported age-related decreases in strength among both males and females in this study. Overall, male participants were stronger than the female participants. However, significantly fewer women were referred for education based on their grip strength scores. The rates of referral for education are a concern regarding core- and leg strength for more than one-third of athletes over the age of 30. These findings suggest that a substantial proportion of Special Olympics athletes would benefit from additional strength and conditioning training.